Perencanaan Hotel (5 Lantai + 1 Basement) dengan Sistem Rangka Pemikul Momen Menengah Di Wilayah Surakarta - HANANTO, ARY TRI (2016)
5 FLOORS + 1 BASEMENT HOTEL DESIGN WITH BEARERS INTERMEDIATE MOMENT RESISTING FRAME SYSTEM IN SURAKARTA ABSTARCTION ARY TRI HANANTO Civil Engineering Program of Engineering Faculty Muhammadiyah University of Surakarta Jl. A. Yani Tromol Pos 1 Pabelan Kartasura 57102 Telp 0271 717417 e-mail : a3.hananto@gmail.com Surakarta is a growing city in the tourism sector and become a destination for traveler and tourists. Business growth also had an impact to around the city of Surakarta. The necessity of a place to stay become an interesting consideration to planned a hotel with 5 floors + 1 basement using Bearers Intermediate Moment Resisting Frame System in Surakarta. The building structure's planning have to considering the capability of the structural, architectural and economical. The design of the hotel refers to the regulatory standards (SNI) version that has been published that is the ISO-1726: 2012 (The Earthquake Resistance For Building and Non-Building Structure Procedures) and ISO 2847: 2013 (Building Code Requirements for Structural Concrete). The Design of the building includes the main structure (the columns and beams structure), the structure of the plates (roof plate, floor plate, basement walls and stairs) and the roof structure (elbow double steel frame). With the location of the building in the area of Surakarta and based from classification calculation, the soil sites included as SD (land being) category, the obtained value of SDS and SD1 are 0.579 and 0.360, so the classification of Seismic Design Category (SDC) for this plan included as KDS D (risk of a large earthquake). For the necessity of the planning of earthquake loads on the building SRPMM, virtue factor of buildings using Ie with value 1 (residential, risk category IV) factor modification response (R) is 5, quality of the concrete using fc '25 MPa, steel reinforcement BJTD 400 MPa and BJTP 240 MPa. The dimensional of beam structure that planned is 350/700 for each floor, while for the column structure, for the basement until the third floor using 500/600 mm dimension, for the 4th floor and 5th floor using 450/550 mm 400/500 mm dimensions. Lower structure planned using pile foundation with 300/300 dimensions for each pole and 8000 mm long, poer using 2500 mm x 2500 mm dimension, 1000 mm thick, and the depth of the foundation reaches 16000 mm. Keyword : design, poer, bearers intermediate moment resisting frame system, building structure, pile:foundation.